An Indonesia Experience: Does Zakat Enhance Macroeconomic Variables? - Annisa Sasri Anindya; Laila Masruro Pimada (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
Zakat is one of the duties that a Muslim must do. As a country with the largest Muslim population, Zakat potential in Indonesia reaches 327 T (trillion) every year. Seeing the enormous potential, this research will examine Zakat distribution through human development, unemployment, and poverty in Indonesia between 2011-2021. However, unfortunately, Indonesia's total collection of Zakat in 2021 only reached around 517,2 billion. With a total of 44 samples, the data were processed using Vector Auto-Regressive (VAR) with Vector Error Correction Model (VECM) estimation. In the short term, based on data processing results, Zakat's distribution does not affect human development, unemployment, and poverty. Nevertheless, in the long term, it is known that the distribution of Zakat affects human development, unemployment, and poverty. The results of this research are expected to be evaluation material for the government, Zakat management institutions, and Muslim society to pay more attention to the urgency of Zakat on human development, unemployment, and poverty.